Effect of ubiquinol supplementation on biochemical and oxidative stress indexes after intense exercise in young athletes. (1st January 2018) - Orlando, Patrick; Silvestri, Sonia; Galeazzi, Roberta; Antonicelli, Roberto; Marcheggiani, Fabio; Cirilli, Ilenia; Bacchetti, Tiziana; Tiano, Luca
ABSTRACT: Objectives: Physical exercise significantly impacts the biochemistry of the organism. Ubiquinone is a key component of the mitochondrial respiratory chain and ubiquinol, its reduced and active form, is an emerging molecule in sport nutrition. The aim of this study was to evaluate the effect of ubiquinol supplementation on biochemical and oxidative stress indexes after an intense bout of exercise. Methods: 21 male young athletes (26 + 5 years of age) were randomized in two groups according to a double blind cross-over study, either supplemented with ubiquinol (200 mg/day) or placebo for 1 month. Blood was withdrawn before and after a single bout of intense exercise (40 min run at 85% maxHR). Physical performance, hematochemical parameters, ubiquinone/ubiquinol plasma content, intracellular reactive oxygen species (ROS) level, mitochondrial membrane depolarization, paraoxonase activity and oxidative DNA damage were analyzed. Results: A single bout of intense exercise produced a significant increase in most hematochemical indexes, in particular CK and Mb while, on the contrary, normalized coenzyme Q10 plasma content decreased significantly in all subjects. Ubiquinol supplementation prevented exercise-induced CoQ deprivation and decrease in paraoxonase activity. Moreover at a cellular level, in peripheral blood mononuclear cells, ubiquinol supplementation was associated with a significant decrease in cytosolic ROS while mitochondrial membrane potential and oxidative DNA damage remained unchanged. Discussion: Data highlights a very rapid dynamic of CoQ depletion following intense exercise underlying an increased demand by the organism. Ubiquinol supplementation minimized exercise-induced depletion and enhanced plasma and cellular antioxidant levels but it was not able to improve physical performance indexes or markers of muscular damage.